Optimizing Community-Based Waste Management: A Business Model Canvas Approach to Waste Bank Sustainability - Feronica Simanjorang; Rahma Hayati Harahap (Asian Journal of Environmental Research, 2026)
Urban waste management in Indonesia is becoming increasingly challenging due to rapid population growth and changing consumption patterns that generate larger volumes of waste. One alternative approach that supports the principles of the circular economy is community-based waste management through waste banks. This study aims to analyze the business model of the Karya Mandiri New Waste Bank in Tebing Tinggi City using the Business Model Canvas (BMC) framework and to formulate development strategies for its sustainability. This study employs a qualitative descriptive approach with data collected through interviews, observations, and documentation. Findings indicate that the waste bank has implemented essential waste management activities, including collection, sorting, and environmental education programs. However, several obstacles still hinder its operational sustainability, such as limited community participation, inadequate resources, and unstable revenue streams. BMC analysis indicates that key elements, particularly the value proposition, channels, and revenue streams, have not been effectively optimized. Therefore, strategic improvements are needed through strengthened partnerships, increased community participation, diversification of revenue sources, and the utilization of digital technology. Optimizing the waste bank business model can help reduce landfill leakage, prevent marine plastic pollution, lower greenhouse gas emissions, and support Sustainable Development Goals (SDGs) 12 and 14 through sustainable waste management practices.